Microlearning on TikTok: Developing Creativity and Communication for Vocational Students - Atadila Berliani Daniswara; Aris Budianto; Nurcahya Pradana Taufik Prakisya (Journal of Pedagogy and Education Science, 2026)
Non-technical skills (soft skills), such as creativity and oral communication, have become increasingly important for Vocational High School graduates in the Industry 4.0 era; however, their systematic integration into the curriculum remains limited. This study aimed to develop and examine the feasibility and preliminary effectiveness of a TikTok-based microlearning platform to support the development of vocational students’ soft skills. The study employed a research and development approach using the ADDIE model and involved 32 vocational students in Boyolali, Central Java, Indonesia. Data were collected through expert validation, student response questionnaires, and a pretest–posttest design. Expert validation indicated that the developed media met high feasibility criteria, with an average score of 88% from media and material experts. Student responses suggested a positive level of acceptance, with an average score of 83.6%. The pretest–posttest results showed modest increases in average scores for creativity (2.44 points) and oral communication (8.12 points). These findings suggest that TikTok-based microlearning has potential as a supportive and engaging tool for facilitating the development of vocational students’ soft skills, although further studies with larger samples and comparative designs are recommended to confirm its effectiveness.